Diffuse Large B-Cell Lymphoma in an Adolescent Male Presenting as Ureteral Stricture - Christopher D. Jaeger; Kelly L. McAlvany; Shannon N. Zingula; Stephen A. Kramer; Candace F. Granberg (Case Reports in Radiology)
Lymphoma may affect the ureter in cases of retroperitoneal involvement. We present a case of an adolescent male found to have non-Hodgkin lymphoma initially presenting as ureteral stricture evident on imaging. He was treated and responded to multiagent chemotherapy with resolution of both the lymphoma and the ureteral stricture. Although rare, non-Hodgkin lymphoma should be included in the differential diagnosis of pediatric patients with noncalculous, idiopathic ureteral strictures.